2017
DOI: 10.1080/13825585.2017.1360835
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in affective and cognitive empathy: self-report and performance-based evidence

Abstract: The correlation between age and empathy is not clear, with prior findings yielding mixed and inconsistent results. Here, we distinguished between two aspects of empathy and respectively investigated the effects of age on the affective and cognitive facets of empathy using a self-report measure (interpersonal reactivity index, IRI) and performance-based tasks (viewing films). The results showed that older adults manifested age-related deficits in both trait and state cognitive empathy, with the latter being pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 87 publications
3
49
2
1
Order By: Relevance
“…The age changes in affective empathy were related with the emotional valence of the stimuli used. Older participants showed more empathic concern and less personal distress in situations that presented negative emotions, whereas for situations that presented positive emotions, older participants demonstrated more empathic concern and personal distress [31]. This dissociation between cognitive aspects of others' understanding and affective aspects, in which the first showed a decrease and the second presents no change or increases with age, is confirmed in other independent studies [32,33]; the following are some conflicting results [34,35].…”
Section: Empathy Across the Life Spansupporting
confidence: 64%
“…The age changes in affective empathy were related with the emotional valence of the stimuli used. Older participants showed more empathic concern and less personal distress in situations that presented negative emotions, whereas for situations that presented positive emotions, older participants demonstrated more empathic concern and personal distress [31]. This dissociation between cognitive aspects of others' understanding and affective aspects, in which the first showed a decrease and the second presents no change or increases with age, is confirmed in other independent studies [32,33]; the following are some conflicting results [34,35].…”
Section: Empathy Across the Life Spansupporting
confidence: 64%
“…Our results indicated a negative association between physician age of 45–54 years and being a high empathy scorer, yet no association between empathy and length of time since specialization, as a measure of clinical experience. Based on the results of prior demographic studies, we expected cognitive empathy to decrease with age [ 32 ]. However, others have found that this relationship did not hold when the personal relevance of the task was controlled for [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We expected this to remain true in our study population. Age was included as cognitive empathy may decrease with older age [ 32 ]. We predict a similar trend will exist in this study.…”
Section: Methodsmentioning
confidence: 99%
“…be evident for both components of ToM. Prior literature has shown that older adults often exhibit greater social cognitive difficulties than younger adults ( Grainger et al, , 2020Henry et al, 2013;Sun et al, 2017). Because of this, age was included as a predictor variable in the meta-regression analyses.…”
mentioning
confidence: 99%